Hippocampus - related cognitive and affective impairments in patients with breast cancer: a systematic review - Peukert, Xenia; Steindorf, Karen (Frontiers in oncology, 2020)
Background: Although improvements in medical treatment lead to a stably rising survival rate of breast cancer patients (BCP), it is associated with a decrease in cognitive and affective function. The hippocampus, a brain region with a high influence on both cognitive and affective function, is increasingly becoming the focus of current research because of its high vulnerability to adverse direct (chemotherapeutic agents, endocrine therapeutic agents and radiation) or indirect (stress and other psycho-social factors) treatment-related effects. Methods: This systematic review analyses current data on literature combining hippocampus-related brain changes due to breast cancer treatment with associated cancer-related cognitive and affective impairments (CRCI/CRAI). The seven studies that met the inclusion criteria consisted of six cross-sectional studies and one longitudinal study. Results: The study results indicate hippocampal differences across all types of treatment. Those differences include volume loss, deformation as well as changes in functional connectivity. They are associated with CRCI, revealing executive function as well as working memory, episodic memory, and prospective memory as the most affected domains. Although an interaction between hippocampus-related brain changes, CRCI, and CRAI can be hypothesized, CRAI are less reflected in current research. Conclusions: More research including longitudinal assessments with better overall methodology is needed to fully understand the interaction between hippocampal and both CRCI and CRAI due to breast cancer treatment. The long-term goal should be to integrate these comprehensive findings into everyday medical practice and contribute to a higher quality of life and higher chance of survival for the increasing number of BCP.
Gesehen am 29.04.2020